2012
DOI: 10.1038/nsmb.2381
|View full text |Cite
|
Sign up to set email alerts
|

Dxo1 is a new type of eukaryotic enzyme with both decapping and 5′-3′ exoribonuclease activity

Abstract: Summary Recent studies showed that Rai1 is a crucial component of the mRNA 5′-end capping quality control mechanism in yeast. The yeast genome encodes a weak homolog of Rai1, Ydr370C, but little is known about this protein. Here we report the crystal structures of Kluyveromyces lactis Ydr370C and the first biochemical and functional studies on this protein. The overall structure of Ydr370C is similar to Rai1. Ydr370C has robust decapping activity on RNAs with unmethylated caps but it has no detectable pyrophos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
160
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(164 citation statements)
references
References 43 publications
4
160
0
Order By: Relevance
“…Multiple Nudix family members can decap mRNA in vitro and likely in cells, and experiments are under way to determine the latter. The recent demonstration that the yeast Rai1 (Xiang et al 2009;Jiao et al 2010) and Dxo1 (Chang et al 2012) proteins, which are not members of the Nudix family of hydrolases, also contain decapping activity that preferentially functions on incompletely capped mRNAs, strongly suggests that there may yet be additional uncharacterized decapping proteins that modulate mRNA decay in cells. Furthermore, the surprising ability of all the decapping-competent Nudt proteins to also function on unmethylated capped RNAs to varying degrees raises an interesting question of whether these proteins may also function on incompletely capped mRNAs in cells and how they may be regulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple Nudix family members can decap mRNA in vitro and likely in cells, and experiments are under way to determine the latter. The recent demonstration that the yeast Rai1 (Xiang et al 2009;Jiao et al 2010) and Dxo1 (Chang et al 2012) proteins, which are not members of the Nudix family of hydrolases, also contain decapping activity that preferentially functions on incompletely capped mRNAs, strongly suggests that there may yet be additional uncharacterized decapping proteins that modulate mRNA decay in cells. Furthermore, the surprising ability of all the decapping-competent Nudt proteins to also function on unmethylated capped RNAs to varying degrees raises an interesting question of whether these proteins may also function on incompletely capped mRNAs in cells and how they may be regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Having recently demonstrated that a subclass of decapping enzymes preferentially functions on incompletely capped mRNAs lacking the N7 methyl moiety (Jiao et al 2010;Chang et al 2012), we tested the capacity of the Nudix proteins to decap unmethylated capped RNA. Consistent with a previous report, Nudt16 hydrolyzed the GpppRNA unmethylated capped RNA and generated GMP decapping product ( Fig.…”
Section: Identification Of Mammalian Nudix Proteins Possessing Decappmentioning
confidence: 99%
“…tRNA intron turnover-healing and decay and Dxo1, which is primarily cytoplasmic (Chang et al 2012), were examined. There is no accumulation of tRNA introns in RNAs from dxo1D or rai1D cells (Fig.…”
Section: The Trna Ligase Rlg1 Phosphorylates Trna Introns Prior To Dementioning
confidence: 99%
“…[55][56][57] Although the efficiency of silencing was very high for both proteins (Fig. S11A, D), similarly to hXRN2 downregulation we did not observe any changes in the pattern of processing at site A 1 upon hUTP24 dysfunction (Fig.…”
mentioning
confidence: 99%